We are given that a1 + a2 + a3 + ... + an = (5n^2+6n).

Sn = a1 + a2 + a3 + ... + an = (5n^2+6n).

Sn+1 = a1 + a2 + a3 + ... + an + an+1 = (5(n+1)^2+6(n+1)).

Sn+1 - Sn

=> a1 + a2 + a3 + ... + an + an+1 - a1 + a2 + a3 + ... + an = (5(n+1)^2+6(n+1)) - (5n^2+6n)

=> an+1 = 5n^2 + 5 + 10n + 6n + 6 - 5n^2 - 6n

=> an+1 = 5 + 10n + 6

=> an+1 = 10n + 11

=> an = 10(n-1) + 11

=> an = 10n - 10 + 11

=> an = 10n + 1

a1 = 10n + 1 = 11

**The required value of an = 10n + 1 and a1 = 11**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now